Decolonisation of education in South Africa: Challenges to decolonise the university curriculum - Du Plessis, P. (South African Journal of Higher Education, 2021)
Leadership matters in the engagement and achievement of students. There is a growing demand for research in the African context as much of the research in this area has emanated from the context of western influences. Through the use of narratives, this qualitative study examines the challenges of five university heads of departments in South African universities to gain deeper insights into the leadership challenges, practices and theorising within a post-colonial context such as that which exists in South Africa. Utilising a decolonised education and a social justice leadership discourse framework, the tensions, challenges and complexities inherent in the heads of department’s leadership practices are explored. Educational leaders in developing countries face problems that are different from their Western counterparts and as such, leadership practices and theorising must be contextualised. Findings support a decolonised approach to education, tensions exist in practice regarding the manifestation of social issues in universities, and the need for leadership development that is grounded in South African knowledge and experiences.